Treatment for plano-valgus foot in children with subtalar arthroereisis. A review - Pardus, Kamila; Stencel-Gabriel, Krystyna; Hajzyk, Marcin; Pilecki, Zbigniew (Journal of Education, Health and Sport, 2024)
Plano-valgus foot is a common problem among children and adolescents. The problem is most often noticed in early childhood, as this is the period when the arches of the foot should achieve a normal structure through the disappearance of the fat pad that is present from birth. During this period, the child’s skeletal system is very malleable and its remodelling can be considerably influenced by additional factors. This is due to the high amount of cartilage tissue present in a child’s skeletal system. Plano-valgus foot can be treated with non-operative methods, such as physiotherapy or the use of orthopaedic supplies, such as suitable orthopaedic insoles. Unfortunately, non-operative treatment is not always sufficient. If physiotherapy does not achieve the expected results, a physician may opt for surgical treatment to restore a correct foot alignment. The most commonly performed plano-valgus foot procedure is subtalar arthroereisis. It is a minimally invasive procedure that takes approximately 10–30 minutes to perform. During the procedure, appropriate implants of various types and sizes are inserted into the tarsal sinus to reduce excessive foot pronation. Studies have shown that the procedure is beneficial to the patient, as it positions the foot correctly and children can return to performing physical activities without experiencing pain and/or rapid muscle fatigue in the foot area. The most commonly used measurements to assess the effects of plantar arthrodesis are those calculated from X-rays, such as Meary’s angle, calcaneal inclination pitch angle (CP), talocalcaneal angle (Kite’s angle), and surveys using The American Orthopaedic Foot and Ankle Society’s (AOFAS’s) ankle and hindfoot scoring system.